A Simple Way to Obtain a Decachloro Derivative of Cobalt Bis(dicarbollide) - Sergey A. Anufriev; Marina Yu. Stogniy; Igor B. Sivaev (Reactions, 2023)
A simple synthetic way to obtain a decachloro derivative of cobalt bis(dicarbollide) has been found. The reaction of cesium salt of cobalt bis(dicarbollide) anion with aluminum chloride in chloroform under reflux conditions results in Cs[3,3′-Co(4,7,8,9,12-Cl5-1,2-C2B9H6)2] of high purity and good yield.